Government's record on health services - Labour Party (Great Britain). Advisory Committee on Public Health
1927-09 1927 1920s 11 pages Private and Confidential September, 1927 No. 148 LABOUR PARTY RESEARCH AND INFORMATION DEPARTMENT PUBLIC HEALTH ADVISORY COMMITTEE GOVERNMENT'S RECORD ON HEALTH SERVICES It is generally accepted that one of the principal functions of any Government is to use both its legislative and administrative power in the direction of safeguarding the health of the community by measures which can only be initiated and enforced by collective effort. The extent to which individual action can promote good health is necessarily limited, particularly in the more thickly populated centres and it is therefore the business of the Government of the day to apply its authority to ensure that what can only be secured by national authority should be enforced. Judged by this test of good government the present Conservative administration is found wanting, as is at once seen by a glance at their record on various matters vital to the health of the community. National Health Insurance By the Government’s 1926 Economy Act they withdrew from National Health Insurance Services the annual sum of £2,800,000 which capitalised at four per cent. is equivalent to £70,000,000. The action of the Government in taking this huge sum of money from the services "for the prevention and cure of sickness" is not only to be condemned because of its anti-social effects, but because of the questionable method adopted in obtaining possession of this amount. In short the Government in order to relieve the tax-payer to the extent of about ½d in the £. appropriated a sum of money which has been discovered by the Royal Commission on Health Insurance and recommended by them as being available for extended health insurance benefits. 292/840/1/15